Too sick for drugs. Too knotty for principles. Scientific research, ethics and cinema - Marino Cattorini, Paolo (Medicina e Morale, 2019)
A narrative approach to biomedical ethics helps to prevent conceptual abstractions and moralistic deductions, even within the context of the dilemmas raised by pharmacological research. Ethical principles cannot be mechanically applied to concrete situations. First of all, we need to discern the meaning of an action in the light of the whole human story in which this action is inscribed. Moreover, the various ethical theories (which link, structure and prioritize principles) rest on original stories, on visions of the world, which outline ideal examples of behavior. This article specifies each ethical principle, comparing it to cinematographic plots and literary images, in order to verify the pertinence of the rules and judgments formulated regarding problematic aspects of scientific investigation. These films usefully trace social representations and emotionally complex individual experiences, preparing a public debate and responsible deliberation.